Crack growth simulation of bulk and ultrafine grained 7075 Al alloy by XFEM. (1st January 2012) - Das, Prosenjit; Singh, Indra Vir; Jayaganthan, R.
In the present work, the effect of cryorolling on tensile strength, impact toughness and fracture energy of 7075 Al alloy has been studied experimentally, and quasi-static crack growth simulation has been performed by extended finite element method (XFEM) for both UFG and bulk Al Alloys. The 7075 Al alloy is rolled for 40% and 70% thickness reduction at cryogenic temperature. The microstructural characterisation of the alloy was carried out by using field emission scanning electron microscopy (FESEM). The cryorolled Al alloy after 70% thickness reduction exhibits fully formed ultrafine grain structure (grain size 600 nanometres) throughout the cross section as observed from FESEM micrographs. The mechanical properties of both alloys are obtained by tensile and Charpy impact testing. In XFEM simulations, this impact energy is used as a crack growth criterion for elastic-plastic ductile fracture. In XFEM, a discontinuous function is used to model the region behind the crack tip, whereas a crack tip is modelled by near-tip asymptotic functions.